THE DYNAMICS OF THE DEVELOPMENT OF MINANGKABAU HISTORIOGRAPHY - Ahmad Fadil (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2026)
The historiography of Minangkabau reflects a dynamic evolution from oral traditions to contemporary decolonial scholarship. Historically, Minangkabau historiography emerged from pre-colonial traditions such as tambo, kaba, and tarombo, which functioned as moral and cosmological narratives sustaining social cohesion and identity. During the colonial era, European scholars reframed Minangkabau history within ethnographic and administrative frameworks, producing positivist and Eurocentric narratives that marginalized local epistemologies. In the national period (1950–1980s), historiography was institutionalized within Indonesian academia, adopting modern historical methods but often subordinated to nationalist ideology. The contemporary phase, however, marks a paradigm shift toward critical and decolonial approaches emphasizing local agency, microhistory, and reinterpretation of indigenous sources. This study employs a qualitative historiographical analysis using postcolonial and decolonial theoretical frameworks to trace epistemological and ideological transitions in Minangkabau historical writing. Findings reveal that epistemological shifts from oral to written, from colonial objectivity to reflective locality were shaped by power relations, academic paradigms, and cultural negotiation. Ideologically, historiography moved from adat-based cosmology, through colonial hegemony, to national integration and finally to local reclamation. The study concludes that Minangkabau historiography represents an ongoing intellectual resistance, where decolonial narratives reclaim historical agency and restore indigenous knowledge systems within modern scholarship.